Dampak Kenaikan Tarif PPN 12% terhadap UMKM di Indonesia pada Era Transformasi Pajak Digital 2025 - Septiyani Wulandari; Imahda Khoiri Furqon (Indonesian Journal of Applied Accounting and Finance, 2025)
This study aims to analyze the impact of the increase in Value Added Tax (VAT) rate to 12% on Micro, Small, and Medium Enterprises (MSMEs) in Indonesia during the 2025 digital tax transformation era. This policy, as regulated in Law Number 7 of 2021 on Tax Regulation Harmonization, boosts state revenue but burdens MSMEs contributing 61% to national GDP. The research method employs library research with a descriptive analytical approach, examining literature, regulations, and recent reports from the last five years to identify fiscal risks and digital adaptation. The results indicate economic impacts such as a 15% rise in production costs, revenue decline due to inflation, and disparities between small and large MSMEs. Administrative challenges arise from integrating Coretax and e-invoicing systems, demanding low digital literacy among MSMEs. Adaptation strategies include utilizing digital platforms for efficient reporting, while policy recommendations encompass technology subsidies, mass education, and tax incentives for compliant MSMEs. The novelty of this research lies in an integrative model combining tax burden theory with technology acceptance model in the 2025 digital context, filling gaps in previous studies that lack focus on real-time tax transformation. The contributions provide practical insights for the Directorate General of Taxes in developing mitigation programs, as well as a theoretical model for taxation studies in developing countries, thereby supporting MSMEs' sustainability as the backbone of inclusive economy amid global fiscal turbulence.